Antihyperglycemic Effect and Antioxidants Properties of Black Rice (Oryza sativa L. indica) Cereal and Anthocyanin Extract on Health and Histopathology of Hyperglycemic Rats - Krisbianto, Oki; Astuti, Mary; Marsono, Yustinus (Pakistan Journal of Nutrition, 2016)
Black rice (Oryza sativa L. indica) is rich in anthocyanin hence it could be used as functional food such as cereal for hyperglycemic patient. Black rice cereal supplemented with black soybean (Glycine max L. Merr) (RSC) was prepared as isocaloric feed for three groups of hyperglycemic rats. The first group (F0) was treated only with RSC, while the other two also receive 40 ppm (F4) and 80 ppm (F8) black rice bran anthocyanin extract (BRE). Non- hyperglycemic and hyperglycemic rats which were fed with standard feed were used as control (C) and hyperglycemic group (H) respectively. After 6 weeks experiments, blood glucose level, insulin resistance and MDA value were decreased in treatment groups, which were more significant in F4 and F8 than F0, while FRAP was increased. RSC and BRE alleviated inflammatory and steatosis in pancreas, liver and kidney as shown by the tissue preparation with Hematoxylin and Eosin (H &E) staining.